843 Hospitalisation data of children with SARS-CoV-2 infection in Malta. (17th August 2022) - Gray, Gabrielle de; Pace, David
Abstract : Aims: Two years into the COVID-19 pandemic, there is better understanding of the clinical impact on children. We aimed to assess hospitalisation data for all children admitted with SARS-CoV-2 infection at Mater Dei Hospital Malta, from March 2020 to December 2021. Methods: Case details were gathered from ward documentation. Results of investigations, clinical details on severity of infection and management were obtained from electronic records. Results: A total of 105 children were admitted with a median age of 1.8 years (range 1 month-15 years) of who 50% were male. COVID-19 PCR results were positive prior admission in 44.7% and found to be positive after being admitted in 55.2%. Symptomatic COVID-19 was the sole diagnosis in 45%, 10% had a dual diagnosis, 12% were asymptomatic and incidentally diagnosed after being admitted for an unrelated pathology, and 33% had incomplete documentation. The median duration of hospitalisation was 1 day. Most presented with fever (59%); this being the only symptom in 23.5% whilst others had accompanying respiratory (13.6%) and gastrointestinal (12.6%) symptoOverall, the commonest symptoms were cough (9.8%) and vomiting (8.5%). Complete blood counts and C-reactive protein were largely normal in all. Chest X-Ray, done in 27% of cases, was normal in 89%. Abnormalities included perihilar infiltrates and one was found to have an unrelated upper mediastinal mass. Management mostly involved observation; antibiotics were prescribed in 23% of cases (mainly for suspected pneumonia). Only 1.4% of cases required minimal oxygen via facemask. Conclusion: Children below 2 years of age are more likely to be admitted to hospital with SARS-CoV-2 related symptoMany are discharged after exclusion of an alternative serious diagnosis, with the majority having normal blood investigations and chest X-ray findings.